2014
DOI: 10.1111/cdep.12079
|View full text |Cite
|
Sign up to set email alerts
|

The Spacing Effect in Children's Generalization of Knowledge: Allowing Children Time to Forget Promotes Their Ability to Learn

Abstract: Distributing learning events in time promotes memory to a greater degree than massing learning together in immediate succession, a phenomenon known as the spacing effect. In this article, I review research on the spacing effect in children's acquisition and generalization of conceptual knowledge. For decades, researchers hypothesized that spaced learning should deter generalization because the forgetting that occurs between learning events limits children's ability to retrieve prior learning. However, new rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 38 publications
4
70
0
Order By: Relevance
“…For example, according to forgetting-as-abstraction account (see Vlach, 2014, for a review), children's forgetting during the temporal gaps between category exemplar presentations promotes categorization and generalization. Across experiences with category exemplars, relevant features are likely to be present in multiple exemplars, reactivating this feature in memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, according to forgetting-as-abstraction account (see Vlach, 2014, for a review), children's forgetting during the temporal gaps between category exemplar presentations promotes categorization and generalization. Across experiences with category exemplars, relevant features are likely to be present in multiple exemplars, reactivating this feature in memory.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent research has suggested that forgetting and retrieving information are critical processes in children's categorization of objects (Vlach, et al, 2008; Vlach, Sandhofer & Bjork, 2014; Vlach, Ankowski, & Sandhofer, 2012). In particular, having higher retention for features that are likely to be more relevant to categorization (i.e., shape) and lower retention of features that are likely to be less relevant to categorization (i.e., size) can promote generalization (forgetting-as-abstraction account; Vlach, 2014). …”
mentioning
confidence: 99%
“…This connection is strengthened by recent work demonstrating that many of the same factors that influence memory-such as massed versus spaced practice-also influence children in statistical learning tasks such as discovering categories (e.g. [55,56]). To the extent that language processing is accomplished by the same kinds of mechanisms studied in more traditional memory paradigms, it may be the case that many aspects of language learning and comprehension are constrained by the way in which stimuli are encoded, stored and accessed in memory (e.g.…”
Section: Implications Of a Memory-based Perspectivementioning
confidence: 99%
“…His studies were based on the self-testing of acquired memory for lists of syllables, but the superiority of spaced training has now been established for many additional forms of human learning. For example, spaced learning is more effective than massed learning for facts, concepts and lists 24 , skill learning and motor learning 5,6 , in classroom education (including science learning and vocabulary learning) 79 , and in generalization of conceptual knowledge in children 10 . Spaced training also leads to improved memory in invertebrates, such as the mollusk Aplysia californica 11–14 , Drosophila melanogaster 15,16 and bees 17 , and in rodents 18,19 and non-human primates 20,21 .…”
mentioning
confidence: 99%